Volleyball : skills & drills - Lenberg, Kinda S., ....- (Champaign : Human Kinetics, 2006)
Master volleyball's key techniques help elevate performance in all facets of the sport. Volleyball Skills & Drills teaches the fundamentals to help players master and apply those skills on the court when it counts. Featuring 10 of the sport's best coaches and 75 of their most effective drills, this guide will maximize both the rate and quality of learning, helping players and coaches get the most out of each practice session.
AVCA - American Volleyball Coaches Association
Keywords: Volleybal